Analysis of Pharmacists and Doctors Collaboration in Handling Diabetes Mellitus Patients: Pharmacists Perspective - Fransisca Gloria; Liza Pristianty; Abdul Rahem (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2022)
Background: Diabetes mellitus is a complex disease, a chronic disease which requires continuous medical care. To improve patient clinical outcomes and success in therapy requires an inter professional collaboration. Objective: This study was aimed to analyse the collaboration of physicians and pharmacists in community healthcare centers throughout Surabaya, especially in dealing with diabetes mellitus patients from pharmacist's perspective. Method: This was a cross sectional study that was conducted within 3 months in 63 community healthcare centers in Surabaya with 63 pharmacists as respondents. The instrument used was the “Pharmacists Collaboration Questionnaire” which contained independent variables from Collaborative Working Relationship (CWR) models including exchange characteristics with trust domain, initiation relationship and role specifications. The Dependent variable was collaborative practice. Data analysis used was non-parametric analysis with Rank Spearman Test correlation to determine the relationship between the exchange characteristics variable. Result: The results of data analysis showed that there was a significant relationship (p = 0.000) between each of the three domains and collaborative practice of physician and pharmacist. The initiation relationship pharmacists was a domain that had strongest influence on collaboration practice followed by specification role and trust. Conclusion:  Despite the result that all three domains in CWR had correlation with collaborative practice, further information about the real implementation of collaborative practice.  Keywords: collaboration, diabetes mellitus, intervention, pharmacist and doctor